Development of nanoparticle sensors for the detection and quantification of swine DNA in mixed biological and commercial samples for halal authentication - Md Eaqub, Ali (Universiti Malaysia Perlis (UniMAP), 2014)
Verification of declared components in meats and meat products is essential to ensure transparency in food labeling and to safeguard consumers’ trusts, religious faiths, health, and hard earned fortunes. The annual turnover of the global Halal food market has reached USD 661billion in 2011 and will be proliferating in the coming years. To coup up in highly competitive market and to make an excessive profit, fraudulent labeling of Halal brand is frequently occurring. As pork and pork-derivatives are easily available at cheaper prices, replacement of higher priced Halal meats in commercial meat products with lower valued pork has become quite prevalent. However, the mixing of pork and pork-derived materials in the Halal and Kosher foods is a serious matter as they are not allowed to be consumed by the followers of Islam and Judaism by respective religious laws. Thus, sensitive, dependable, and easy performable analytical tools have long been desired to detect and quantify the minute level of adulterated pork in Halal and Kosher foods. Conventional methods based on polymerase chain reaction (PCR)-based DNA analysis has reached a ceiling stage and has limitations in detecting shorter-length DNA markers which are proven to be survived in the harsh conditions of food processing. Further, PCR-based methods are not only expensive but also needs product authentication to eliminate ambiguity in certain instances. DNA detection using gold nanoparticles (GNPs) is very promising because it does not need any complex and expensive instrumentations and allows rapid and reliable detection of very short-length (15-30 bp) DNA sequences. In this report, we have developed two types of GNP-based sensors. The first one is the colorimetric sensor that allowed visual detection of PCR amplified and non-amplified swine DNA markers (27 and 25 nucleotides) within 10 min without any instrumental aids in a mixed background of processed and unprocessed meat products. It also permitted the verification of the visually determined results by the distinct features of the absorption spectra of the aggregated and non-aggregated GNPs. The detection limit (DL) of this method varied between 4-6 ng μL-1 of porcine genomic DNA. The second one was the hybrid nanobioprobe that covalently integrated a fluorophore labeled 27-nucleotide AluI-fragment of swine mitochondrial cytochrome b (mt-cytb) gene. It allowed simultaneous detection and quantification of porcine muticopy mt-DNA targets within 60 min with the help of a cost-effective fluorescent spectroscopy. The DL of this method was 0.42 ng μL-1 of contaminated pork in severely autoclaved pork-beef binary mixture in which longer-size PCR template were broken down to smaller fragments leading to detection failure by the PCR- methodology. The shorter-lengths DNA markers (15-30 bp) suitable for biosensor application were developed by in-silico digestion of swine mt-genome with AluI restriction enzymes. Prior to biosensor applications, the swine specificity of the developed mt-DNA markers was tested by developing a very short (109 bp) PCR-restriction fragment length polymorphism (RFLP) assay as well as a TaqMan probe quantitative real-time PCR (qPCR) assay containing appropriate AluI-sites within the amplicon. Both the PCR-RFLP and qPCR assays were effective to detect as low as 0.0001 ng of pure swine-genomic DNA and 0.001 ng of pork contamination in readyto- eat commercial meat products.